Labour, Migration and the Spatial Fix: Evidence from the UK Food Industry. Issue 5 (10th June 2013) - Scott, Sam
<x xml:space="preserve">Abstract</x> Abstract The paper argues that David Harvey's (1981) concept of the "spatial fix" (Antipode 13(3):1–12) can help us to understand contemporary labour migration. According to Harvey, the spatial fix is a response by capital to periodic crises that may involve both ex situ (finding new markets and production sites) and in situ solutions (importing and/ or improving labour). Drawing on experiences in the UK food industry, via 37 employer interviews, I show that in situ restructuring has become hegemonic and that an associated "good migrant worker" rhetoric has emerged. This rhetoric has two dimensions. Most obviously, low‐wage employers stress the apparently superior hard and soft skills of migrants. Some, however, also link low‐wage immigration to a purposeful shift in power from labour to capital. In both respects, migration functions as a regulatory project and "spatial fix", and employers' "need" for migrant labour is primarily about maximising labour power in downgraded jobs more than about absolute labour shortages. Implications for policy Employer reliance on migrant labour is not new. It is important, therefore, that policymakers do not get too carried away by contemporary low‐wage immigration. Nevertheless, this phenomenon appears to occur even when, in theory at least, employers could recruit domestically. The fact that they do not, demonstrates the ways in which recruitment, even at the bottom of the labour market, is not just about getting people in post, but about getting the right kind of people in post. Labour shortages, then, are an issue of quality and quantity; and employers' ability to use periphery‐to‐core migration to increase both is what constitutes the "in situ spatial fix". The challenge for policymakers is to weigh up the undoubted economic benefits of this "fix" (especially significant for sectors that are undergoing prolonged restructuring, like the UK food industry) against the impact it can have in depressing pay and conditions and further marginalising would‐be domestic workers.